Personalized Travel Itinerary Recommendation Service based on collaborative filtering and IEC - Cong Li; Jianjun Wang; Li Ma; Qing Lu (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
Personalized Travel Itinerary Recommendation Service (PTIRS) is a hot research problem in E-travel information management currently. To improve the problem, in this paper a PTIRS method based on collaborative Altering and IEC is proposed. Firstly the scale of travel itinerary sample set is reduced by collaborative Altering; secondly an IEC algorithm called IMAGA is used to accelerate convergence speed for alleviating the phenomena "user estimating tiredness"; Anally the most satisfactory travel itinerary can be achieved for target user. Simulating experiment show the validity of the proposed method.